Kecemasan Penggunaan Bahasa Asing di Kelas AFL Dewasa : Penelitian - Amira Deani; Ghina’a Jayanthi Putri; Adib Alfalah; Andiana Perizga (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Anxiety is a feeling of fear, tension and apprehension about what’s to come. The purpose of this study was to determine the level of students' anxiety in foreign language learning and to find out the cause of anxiety that occurred in English classroom. The research methodology is descriptive quantitative study. Data collection techniques are questionnaire of foreign language class anxiety scale (FLCAS) adapted from Horwitz, E. K., Horwitz, M. B., & Cope, J. (1986) to determine the level of students' speaking anxiety and to find out the dominant type of anxiety that occurs. Furthermore, a structured interview in order to find the causes of the foreign language anxiety. The writer found that there are 2 students (10.5%) who experience "Very Anxious" level with a range score of 124-165, 7 students (36.8%) who experience “Anxious” level, with a range score of 108-123, 8 students ( 42.1%) who experienced "Mildly Anxious" level with a range score of 87-107, 2 students (10.5%) who experience "relaxed" level with a range score of 66-86, and nothing student (0%) who experience "very relaxed" level with range score of 33-65. Moreover, from the interview, it can be concluded that there are 4 causes of the FLA. They are lack of vocabularies, lack of self-confidence, test anxiety and peer anxiety.